FREQUENCY OF JANUS ASSOCIATED KINASE 2 (JAK2) MUTATION IN PATIENTS OF BCR-ABL NEGATIVE MYELOPROLIFERATIVE NEOPLASMS: JAK2 Mutation - Sadiq, Maj Muhammad Arif; ., Suhaib Ahmed; ., Nadir Ali (Pakistan Armed Forces Medical Journal, 2013)
Objective: To determine the frequency of Janus associated kinase 2 mutation in the patients of BCR-ABL negative classical myeloproliferative neoplasms. Study Design: Cross-sectional descriptive study Place and Duration of Study: Molecular Department of Haematology, Armed Forces Institute of Pathology (AFIP), Rawalpindi from Jul 2011 to Jul 2012. Patients and Methods: Ninety three consecutive patients of Polycythaemia vera (PV), Essential thrombocythaemia (ET) and Idiopathic myelofibrosis (IMF) diagnosed by the conventional haematological criteria were included in the study. All patients were screened for G-T point mutation (V617F) in the JAK2 gene on chromosome 9 by an allele specific PCR. Results: Out of the 93 myeloproliferative neoplasm (MPN) patients, 33(35%) had polycythaemia vera, 36(39%) had essential thrombocythaemia and 24(26%) had idiopathic myelofibrosis. JAK2 mutation was seen in 64/93 (69%) patients including 33/33(100%) in PV, 19/36(52.6%) in ET and 12/24(50%) in IMF. Conclusion: Classical myeloproliferative neoplasms are an important group of heamatological disorder in our country. JAK2 gene mutation is seen in significant proportion of these disorders (69%). JAK2 mutation analysis can be used to differentiate between polycythemia vera and secondary polycythemia in most cases with near certainty, where it was found in 100% of the cases.